Analysis of Mathematical Concept Understanding Ability Based on Learning Styles of Grade XI Students on Circle Geometry - Soldi Saputra, Ade; Muslimahayati, Muslimahayati; Sahanata, Meirisa (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
The purpose of this study was to identify learning styles that show the highest level of achievement and describe students’ mathematical concept comprehension abilities in circle-related content based on visual, auditory, and kinesthetic learning styles. A total of 9 selected students from a total of 26 high school students participated in interviews, conceptual comprehension ability tests, and questionnaires as part of the qualitative descriptive methodology of this study. Based on the findings, 73.08% of students fell into the middle category, 11.54% into the low category, and 15.38% into the high category. There were 11 students with visual learning styles, including 2 in the low category, 8 students in the middle category, and 1 student in the high category. There were 7 students with auditory learning styles who only showed achievements in 2 categories, namely 5 in the middle category and 2 in the high category. There were 5 students with kinesthetic learning styles, among which 1 was in the low category and 4 in the middle category, with none reaching the high category. Therefore, it can be said that the kinesthetic learning type showed the lowest achievement, while the auditory learning style produced the highest achievement. The findings of this study also support the idea that learning style is not the only factor that influences the understanding of mathematical concepts, other additional factors include motivation, prior knowledge, and the teaching methods used.